COMMUNICATION IN THE INITIAL IMPLEMENTATION OF DIGITAL TV MIGRATION IN BEKASI CITY - Sutanto, Vinnawaty; Rahmadiana, Rahmadiana (Universitas Gunadarma, 2024)
The migration from analog to digital television or analog switch-off (ASO) represents a solution to overcome various limitations of analog systems. Digital television offers multicasting capabilities, enabling multiple transmission signals through a single channel, thereby addressing spectrum constraints faced by analog television. This study explores communication strategies during the initial phase of analog switch-off in Bekasi City. Theoretical frameworks like diffusion of innovations highlight the importance of communication in disseminating information and facilitating technology adoption. This research uses qualitative approaches to investigate community responses and satisfaction with digital television. Findings indicate that direct information from local officials and media channels significantly influences public readiness and acceptance of digital television. The study aligns with diffusion theory stages, illustrating how knowledge acquisition, persuasion, decision-making, implementation, and confirmation phases influence community adoption. Effective communication, supported by clear regulations and governmental policies, accelerates technology adoption and enhances user satisfaction. Insights from this study underscore the importance of proactive government support and targeted communication strategies in successful ASO implementation. The findings contribute to understanding how effective communication can facilitate technology transitions and improve broadcast quality and user experience in digital television.